Lysosomal glucocerebrosidase is needed for ciliary Hedgehog signaling: A convergent pathway contributing to Parkinson’s disease - Sreeja V. Nair; Ebsy Jaimon; Ayan Adhikari; Jonas Nikoloff; Suzanne R. Pfeffer (Proceedings of the National Academy of Sciences, 2025)
Parkinson’s disease is characterized by loss of dopamine neurons that project to the dorsal striatum, and mutations in LRRK2 and GBA1 are the most common genetic causes of familial Parkinson’s disease. Previously, we showed that pathogenic LRRK2 mutations inhibit primary cilia formation in rare interneurons and astrocytes of the mouse and human dorsal striatum. This blocks Hedgehog signaling and reduces synthesis of neuroprotective GDNF and NRTN, which normally support dopamine neurons vulnerable in PD. Here, we show that GBA1 mutations also impair Hedgehog signaling and Hedgehog-dependent neuroprotective factor production by a distinct mechanism. Loss of GBA1 activity increases lysosomal accessible cholesterol and thus decreases accessible cholesterol in primary cilia of cultured cells; this change in lipid composition blocks ciliary Hedgehog signaling that depends on accessible cholesterol. Consistent with defects in Hedgehog signaling in the mouse dorsal striatum, GBA1 mutant mice show reduced Hedgehog-induced Gdnf RNA expression in striatal cholinergic interneurons, with no detectable impact on cilia formation. Also, both LRRK2 and GBA1 mutations suppress Hedgehog-induced Bdnf expression in striatal astrocytes. These findings underscore the role of Hedgehog signaling in the nigrostriatal circuit and reveal a convergent mechanism by which distinct LRRK2 and GBA1 mutations may contribute to PD pathogenesis.